156k views
8 votes
What is the expression obtained when the sum of 2a−16abc−45 and 2a+7abc+11 is subtracted from 6a+6abc−30?​

User Sneeky
by
6.2k points

1 Answer

7 votes

Answer:


2a+15abc+4

Explanation:


(2a-16abc-45)+(2a+7abc+11)


\implies 2a-16abc-45+2a+7abc+11

collect and combine like terms:


\implies 4a-9abc-34


(6a+6abc-30)-(4a-9abc-34)

Apply the distributive law
-\left(a-b\right)=-a+b:


\implies 6a+6abc-30-4a+9abc+34

collect and combine like terms:


\implies 2a+15abc+4

User Patrice Neff
by
5.0k points